Längsschnittliche Erhebung pädagogischer Kompetenzen von Lehramtsstudierenden (LEK): Detaillierte Analyse der Ergebnisse von den Universitäten Köln und Paderborn. - Seifert, Andreas; König, Johannes (AEPF-Tagung „Vielfalt empirischer Forschung in Bildung, Erziehung und Sozialisati-on”)

Does emotional narrative context influence retention of newly learned words? - Berner, Anna-Lena; Nachtigäller, Kerstin; Foltz, Anouschka; Rohlfing, Katharina (Poster presented at Narrative, Intervention and Literacy (NIL2012), Paris, France.)

"Scaffolding" the mutual attention of preverbal infants: adaptive multimodal practices in early mother-infant interactions. - Nomikou, Iris; Rohlfing, Katharina

Dokumentation der Studie ProLEG: Professionalisierung von Lehrkräften für einen reflektierten Umgang mit Ethnizität und Geschlecht in der Grundschule. Ausgewählte Daten, Skalen und Ergebnisse (PLAZ-Forum (Lehrerausbildung und Schule in der Diskussion, H. 19))

Rezeption und nationale Identität: Musik zu Schillers „Jungfrau von Orleans“ am Stuttgarter Hoftheater - Tumat, Antje (Musik und kulturelle Identität: Öffentliche Vorträge, Roundtables und Symposien B)

Musik im Theater als Medium kultureller Identitätsstiftung - Schmidt, Beate Agnes; Tumat, Antje (Musik und kulturelle Identität: Öffentliche Vorträge, Roundtables und Symposien B)

Singstimme und Geschlechtergeschichte - Grotjahn, Rebecca (Musik und kulturelle Identität: Öffentliche Vorträge, Roundtables und Symposien A)

„Ein überaus wertvolles poetisches Hilfsmittel“ – Zwischenaktmusik am Stuttgarter Hoftheater - Tumat, Antje (Musik und Theater um 1800. Konzeptionen – Aufführungspraxis – Rezeption)

Convulsive seizure detection using a wrist-worn electrodermal activity and accelerometry biosensor. - Poh, MZ; Loddenkemper, T; Reinsberger, Claus; Swenson, NC; Goyal, S; Sabtala, MC; Madsen, JR; Picard, RW (Epilepsia)

Autonomic changes with seizures correlate with postictal EEG suppression. - Poh, MZ; Loddenkemper, T; Reinsberger, Claus; Swenson, NC; Goyal, S; Madsen, JR; Picard, RW (Neurology)

Focal hand dystonia: lack of evidence for abnormality of motor representation at rest. - Weise, D; Gentner, R; Zeller, D; Nagel, A; Reinsberger, Claus; Rumpf, JJ; Classen, J (Neurology)

Pre- and postictal, not ictal, heart rate distinguishes complex partial and psychogenic nonepileptic seizures. - Reinsberger, Claus; Perez, DL; Murphy, MM; Dworetzky, BA (Epilepsy Behav)

Formfactors of Hollow and Massive Rectangular Parallelepipeds at Variable Degree of Anisometry - Nayuk, Roman; Huber, Klaus (Zeitschrift für Physikalische Chemie)
Abstract The present work is a comparative study on the scattering behaviour of hollow and filled rectangular parallelepipeds. Comparison is based on the model formfactors of rectangular parallelepipeds, which cover the entire regime of variable wall thickness. The entire regime of wall thicknesses has been made available by the present work, which completed the set of formulas by calculating the formfactor for the limit of hollow parallelepipeds with infinitely thin walls, which was still lacking. The formfactors are expressed as a function of the momentum transfer q . Discrimination between massive and hollow structures by means of the q -dependent scattering data SF(q) gets possible once the Guinier radius and the particle volume can be established at the lower limit of q or a power law of SF(q) ∼ q α can be extracted towards large q . Whereas the former requires extrapolation of the scattering data to q = 0 with high accuracy, the latter needs experiments over a very broad q -regime. If experimental data is restricted to a q -regime which includes only the first peak in a Kratky representation of q 2 SF(q) vs. q without giving way to an accurate extrapolation to q = 0 nor to a clear power law in q , discrimination between a hollow and a massive structure gets extremely difficult. Yet, the effect of anisometry is striking and enables extraction of a crude guess of the degree of anisometry already from the first Kratky peak. This could be achieved by introducing a dimensionless parameter established from the width and location of the first Kratky peak.
Keywords: Physical and Theoretical Chemistry

Impact of Sodium Polyacrylate on the Amorphous Calcium Carbonate Formation from Supersaturated Solution - Liu, J.; Pancera, S.; Boyko, V.; Gummel, J.; Nayuk, R.; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Modulated Formation of MOF-5 Nanoparticles—A SANS Analysis - Nayuk, R.; Zacher, D.; Schweins, R.; Wiktor, C.; Fischer, R. A.; van Tendeloo, G.; Huber, Klaus (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Controlling quantum dot emission by integration of semiconductor nanomembranes onto piezoelectric actuators - Rastelli, A; Ding, F; Plumhof, J.D; Kumar, S; Trotta, R; Deneke, C; Malachias, A; Atkinson, P; Zallo, E; Zander, T; Herklotz, A; Singh, R; et al.

Polarization anisotropic luminescence of tunable single lateral quantum dot molecules - Hermannstädter, C; Witzany, M; Heldmaier, M; Hafenbrak, R; Jöns, Klaus D.; Beirne, G.J; Michler, P

Quantum state tomography measurements on strain-tuned In(x)Ga(1−x)As/GaAs quantum dots - Jöns, Klaus D.; Hafenbrak, R; Atkinson, P; Rastelli, A; Schmidt, O.G; Michler, P

New experiments for the quantification of counterion condensation - Huber, Klaus; Scheler, Ulrich (Current Opinion in Colloid & Interface Science)
Keywords: Colloid and Surface Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry; Surfaces and Interfaces

Diva – Die Inszenierung der übermenschlichen Frau. Interdisziplinäre Untersuchungen zu einem kulturellen Phänomen des 19. und 20. Jahrhunderts. Hrsg. von Rebecca Grotjahn, Dörte Schmidt und Thomas Seedorf. Schliengen: Edition Argus 2011. 275 S., Abb., Nbsp. (Forum Musikwis-senschaft. Band 7.) - Tumat, Antje (Die Musikforschung)